2004
DOI: 10.1007/s10571-004-6923-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Regulates the Frequency of Spontaneous Synchronized Ca2+ Spikes Through Group II Metabotropic Glutamate Receptor in Cultured Mouse Cortical Networks

Abstract: 1. Synchronized spontaneous intracellular Ca2+ spikes in networked neurons are believed to play a major role in the development and plasticity of neural circuits. Glutamate-induced signals through the ionotropic glutamate receptors (iGluRs) are profoundly involved in the generation of synchronized Ca2+ spikes. 2. In this study, we examined the involvement of metabotropic glutamate receptors (mGluRs) in cultured mouse cortical neurons. We pharmacologically revealed that glutamate-induced signals through inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We showed that LY341495 did not affect spontaneous Ca 2+ spikes by itself. Yasumoto et al (2004) showed that the inhibition of group II mGluRs by (2S)‐a‐ethylglutamic acid increased the frequency of spontaneous Ca 2+ spikes in primary cultures of mouse cortical neurons. The differences in the effects of group II mGluRs antagonists between our results and their report might be due to the level of the extracellular glutamate concentration in assay buffer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that LY341495 did not affect spontaneous Ca 2+ spikes by itself. Yasumoto et al (2004) showed that the inhibition of group II mGluRs by (2S)‐a‐ethylglutamic acid increased the frequency of spontaneous Ca 2+ spikes in primary cultures of mouse cortical neurons. The differences in the effects of group II mGluRs antagonists between our results and their report might be due to the level of the extracellular glutamate concentration in assay buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as trans‐ACPD and (S)‐4CPG are nonselective mGluR ligands, the contributions of each mGluR subtype to spontaneous Ca 2+ spike formation remain to be clearly determined. Although Yasumoto et al, (2004) showed that a group II mGluR antagonist, (2S)‐a‐ethylglutamic acid, increased the frequency of spontaneous Ca 2+ spikes in primary cultures of mouse cortical neurons, no selective agonist of group II mGluRs has been tested for effects on spontaneous Ca 2+ spikes.…”
mentioning
confidence: 99%